Palladium-Catalyzed Synthesis of Biaryl Ketones via tert-Butyl Isocyanide Insertion - Chen, Zhong; Duan, Huaqing; Jiang, Xiao; Wang, Jinmei; Zhu, Yongming; Yang, Shilin (Synlett, 2014)
A simple and efficient palladium-catalyzed carbonylative Suzuki coupling via tert-butyl isocyanide insertion has been developed, which demonstrates the utility of isocyanides in intermolecular C–C bond construction. This methodology provides a novel pathway for the synthesis of diaryl ketones in moderate to good yields. The approach is tolerant to a wide range of substrates and applicable to library synthesis. A possible reaction mechanism was proposed based on the experimental results.
Keywords: isocyanide; carbonylative Suzuki coupling; palladium catalyst; diaryl ketone; insertion reaction